2023
DOI: 10.1101/2023.11.05.565619
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An intronic copy number variation inSyntaxin 17determines speed of greying and melanoma incidence in Grey horses

Carl-Johan Rubin,
McKaela Hodge,
Rakan Naboulsi
et al.

Abstract: The Greying with age phenotype involves loss of hair pigmentation whereas skin pigmentation is not reduced and a predisposition to melanoma. The causal mutation was initially reported as a duplication of a 4.6 kb intronic sequence inSyntaxin 17. The speed of greying varies considerably among Grey horses. Here we demonstrate the presence of two differentGreyalleles,G2carrying two tandem copies of the duplicated sequence andG3carrying three. The latter is by far the most common allele, probably due to strong sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Based on this result, a new nomenclature for the Grey locus has been established as follows: G1 -one copy, wild type; G2 -two copies, slow greying; G3 -three copies, fast greying (Figure 2b). In contrast to G1/G3 horses that show a high incidence of melanomas, no elevated risk compared with wild-type horses was noted for G1/G2 horses (14). Thus, there is a remarkable dosage effect of the Grey mutation, increasing the copy number of the 4.6 kb STX17 sequence shows a strong positive correlation with both speed of greying and incidence of melanoma (Table 1).…”
Section: Copy Number Variation Determines Speed Of Greying and Melano...mentioning
confidence: 98%
See 4 more Smart Citations
“…Based on this result, a new nomenclature for the Grey locus has been established as follows: G1 -one copy, wild type; G2 -two copies, slow greying; G3 -three copies, fast greying (Figure 2b). In contrast to G1/G3 horses that show a high incidence of melanomas, no elevated risk compared with wild-type horses was noted for G1/G2 horses (14). Thus, there is a remarkable dosage effect of the Grey mutation, increasing the copy number of the 4.6 kb STX17 sequence shows a strong positive correlation with both speed of greying and incidence of melanoma (Table 1).…”
Section: Copy Number Variation Determines Speed Of Greying and Melano...mentioning
confidence: 98%
“…We therefore decided to explore if copy number variation of the 4.6 kb STX17 sequence may explain the dramatic difference in the speed of greying that is present in some breeds, for instance, in Connemara ponies. Copy number variation was determined using digital PCR, whole genome-sequencing and sequence capture followed by Nanopore sequencing ( 14 ). The analysis of a half-sib pedigree segregating for slow and fast greying demonstrated that slow-greying horses carry chromosomes with two tandem copies of the 4.6 kb STX17 sequence, whereas fast greying horses carry a tandem triplication ( 14 ).…”
Section: Copy Number Variation Determines Speed Of Greying and Melano...mentioning
confidence: 99%
See 3 more Smart Citations